2021
DOI: 10.1155/2021/4451533
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic Acid Induces Antiproliferation and Anti-Metastatic Property of Esophageal Cancer Cells via MAPK Signaling Pathways

Abstract: Background. Carnosic acid (CA) is a polyphenolic diterpene extracted from rosemary. Reports have shown that CA possesses anticancer activity. However, whether CA inhibits esophageal squamous cell carcinoma, an aggressive type of esophageal cancer, remains untested. Methods. The effects of CA on cell survival, migration, and apoptosis were evaluated by a combination of MTT, colony formation assay, flow cytometry, and Transwell assay. The potential signaling pathways involved were investigated via Western blot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Treatment of the KYSE-150 cell line with CA (more than 25 µM) resulted in suppression of cell growth, migration, and invasion, which were mediated by impeding JNK, p38 and ERK1/2 pathways. CA caused G2/M phase arrest, which was correlated to the decreased expression of cyclin B1, MDM2, CDC2 and the induction of DNA damage ( Jiang et al ., 2021 ). The elevated levels of P53 binding protein 1 (53BP1), a protein involved in the double-strand repair pathway, and γ-H2AX that serves as a marker for the double-strand break, revealed that apoptosis in treated cells was assisted by DNA damage ( Menon and Povirk, 2014 ; Jiang et al ., 2021 ).…”
Section: The Effect Of Rosmarinic Acid and Carnosic Acid On Different...mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of the KYSE-150 cell line with CA (more than 25 µM) resulted in suppression of cell growth, migration, and invasion, which were mediated by impeding JNK, p38 and ERK1/2 pathways. CA caused G2/M phase arrest, which was correlated to the decreased expression of cyclin B1, MDM2, CDC2 and the induction of DNA damage ( Jiang et al ., 2021 ). The elevated levels of P53 binding protein 1 (53BP1), a protein involved in the double-strand repair pathway, and γ-H2AX that serves as a marker for the double-strand break, revealed that apoptosis in treated cells was assisted by DNA damage ( Menon and Povirk, 2014 ; Jiang et al ., 2021 ).…”
Section: The Effect Of Rosmarinic Acid and Carnosic Acid On Different...mentioning
confidence: 99%
“…CA caused G2/M phase arrest, which was correlated to the decreased expression of cyclin B1, MDM2, CDC2 and the induction of DNA damage ( Jiang et al ., 2021 ). The elevated levels of P53 binding protein 1 (53BP1), a protein involved in the double-strand repair pathway, and γ-H2AX that serves as a marker for the double-strand break, revealed that apoptosis in treated cells was assisted by DNA damage ( Menon and Povirk, 2014 ; Jiang et al ., 2021 ). Furthermore, heightened expression of pro-apoptotic Bax protein, and cleaved caspase-3 with low levels of Bcl 2 was also observed ( Jiang et al ., 2021 ).…”
Section: The Effect Of Rosmarinic Acid and Carnosic Acid On Different...mentioning
confidence: 99%
“…Carnosic acid was demonstrated to inhibit angiogenesis, proliferation and migration of cancer cells [107,108]. Moreover, it induced cell apoptosis and DNA damage and was able to inhibit the mitogen-activated protein kinase (MAPK) signaling pathways [109]. Additionally, carnosic acid can inhibit the growth, cell migration and invasion of human non-small cell lung carcinoma cells (A549) via apoptosis and suppression of the PI3K/AKT/m-TOR signaling pathway [110].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Moreover, carnosic acid ( 14 ) influenced apoptosis pathway by inducing the cleavage of PARP and the expression of caspases 3, 8, and 9. The cell cycle arrest at the G2/M phase as well as the promotion of apoptosis by inducing DNA damage, the inhibition of cell migration, and a coordinated inhibition of extracellular signal-regulated kinase (ERK), p-38, and JNK signalling pathways was observed in esophageal squamous cell carcinoma (KYSE-150), an aggressive type of esophageal cancer [ 85 ].…”
Section: Abietane Skeletonmentioning
confidence: 99%